Achieving climate-smart coffee in East Africa. - Bunn, Christian (International Center for Tropical Agriculture, 2019)
This document presents the results of the coffee climate analysis made for East Africa. It contains some of the maps of future changes in suitability for Arabica and Robusta coffee in East Africa and describes some of the implications for the degree of climate change adaptation required for each zone. This brief is divided in 4 sections to guide adaptation at scale: Towards resilient production at scale, Recommendation domains to scale climate smart coffee, Scaling climate smart coffee, Climate smart coffee practices